The Influence Of Work Motivation And Adaptation Ability On Work Productivity (PT Tjiwulan Putra Mandiri Employee Survey Tasikmalaya City): - Parid, Asep; Barlian, Barin; Arif (Jurnal Pusat Manajemen, 2024)
This research was conducted with the aim of determining the influence of work motivation and adaptability on the work productivity of employees of PT Tjiwulan Putra Mandiri, Tasikmalaya City. The method used in this research is a survey method using data obtained directly through questionnaires distributed to 70 respondents who are employees at PT Tjiwulan Putra Mandiri, Tasikmalaya City. The technique used in the research is multiple linear regression. Based on the research results, it can be seen that work motivation and adaptability simultaneously have a significant effect on the work productivity of employees of PT Tjiwulan Putra Mandiri, Tasikmalaya City. Partial Work Motivation has a significant influence on the work productivity of PT Tjiwulan Putra Mandiri employees in Tasikmalaya City. Partial Adaptation Ability has a significant effect on the work productivity of PT Tjiwulan Putra Mandiri employees in Tasikmalaya City.